From deportation to prison : the politics of immigration enforcement in post/civil rights America - Macias-Rojas, Patrisia (Latina/o sociology series., 2016)
Criminal prosecutions for immigration offenses have more than doubled over the last two decades, as national debates about immigration and criminal justice reforms became headline topics. What lies behind this unprecedented increase? This book unpacks how the incarceration of over two million people in the United States gave impetus to a federal immigration initiative - The Criminal Alien Program (CAP) - designed to purge non-citizens from dangerously overcrowded jails and prisons.